Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. Satrindo Jaya Agropalma Kabupaten Musi Rawas - Fitantina Fitantina; Efrina Masdaini; Devia Salsa Fahriza (Politeknik Negeri Sriwijaya, 2024)
This study aims to determine the effect of workload and work environment on job satisfaction of employees of PT. Satrindo Jaya Agropalma Kab. Musi Rawas either simultaneously or partially. The type of research used is associative. Data collection techniques used in this study are questionnaires and documentation. Population in research at PT. Satrindo Jaya Agropalma Kab. Musi Rawas has 102 employees, and the sample number is 51 employees. The analysis of data used in this study is qualitative quantitative. The analysis technique used is multiple linear regression, f Test, t test and coefficient of determination with a significant level of 10%. The results showed that there is a significant influence of workload and work environment on Employee Job Satisfaction. Partially shows there is a significant influence of workload or work environment on job satisfaction of employees of PT. Satrindo Jaya Agropalma Kab. Musi Rawas. The result of the coefficient of determination adjusted R square is 0.529, this means that the workload and work environment are able to contribute to Employee Job Satisfaction by 52.9%. Â